Chiral Lagrangians for strong decays K1→Kρ(ω) - Nurlan, K.; Issadykov, A.; Janseitov, D.M.; Aznabaev, D.T.; Tyulemissov, Zh. (Recent Contributions to Physics, 2023)
A triangular quark diagram describes the vertex K1Kω with axial-vector, vector, and pseudoscalar mesons is considered in the leading order of 1NC. The application of the obtained vertex to the hadronic decays of the τ-lepton with the production of Kω, Kφ meson pairs in the final state is discussed. Calculation of quark diagrams are considered within the SU(3) symmetric chiral Lagrangians, which describe the interactions of four meson nonets: scalar, pseudoscalar, vector, and axial-vector in the ground and in the first radially excited states. The calculated integral decay widths of K1(1270)→K[ω,ρ] are in the agreement with the experimental data of the BES-III and Belle collaborations obtained at the BEPC II and KEK colliders. It is shown that the axial-vector channel with the intermediate meson K1A with quantum numbers JPC=1++ plays a dominant role in describing the decay widths of τ→K[ω,ρ]ντ. In lepton decays, the contact channel and the channel with the axial vector meson K1A are taken into account. The first of them is related with the intermediate W boson, which products a meson pair. The second channel is related with the intermediate W boson, which transits into the axial vector state K1A and also products meson pairs. Consideration of these two channels independently of each other allows us to study the processes in more detail. The splitting of the strange axial vector state K1A into two physical mesons K1(1270) and K1(1400) due to the mixing of axial vector mesons from nonets 3P1 and 1P1 is also taken into account. The negative interference of the contact channel with the axial vector channel is established. The dependences of the integral decay widths of τ→K[ω,ρ]ντ on the value of the mixing angle of axial-vector mesons K1A and K1B are studied. A comparative analysis of the results with experimental data and theoretical estimates of other authors is carried out. The obtained theoretical predictions are in satisfactory agreement with the experimental data.